Role of Artificial Intelligence in Indian Education System - Saxena, Rajesh (Integrated Journal for Research in Arts and Humanities, 2022)
Computer is being used in the field of education for many years and we have got mixed results from it. Although new discoveries in the field of Artificial Intelligence (AI) have shown very positive results in the field of education. AI technology has a very old history which is changing with the times and continuously advancing. This technology is completely based on intelligent agents who learn from the environment around them and take action based on that to maximize their chances of success. AI is a technology made up of machine and computer program that tries to solve problems independently like humans, draws conclusions and takes the right decision based on that. Most artificial intelligence systems have learning capabilities that allow people to improve their performance over time. Recent research on AI tools, including machine learning, deep learning and predictive analysis, aims to enhance the ability to plan, learn, reason, think and take action. In this paper, I will try to explain modern AI techniques and the use of AI in various fields of education.